The Effects of Auditory, Intellectually, and Repetition (AIR) Learning Model to Problem Solving Skills of the Students Grade XI IPA of SMAN 2 Banguntapan on the Subject of Kinetic Theory of Gases - Khoeriyah, Nilatul; Widayanti, Widayanti (Proceeding International Conference on Science and Engineering, 2017)
The purpose of this research is to know the effects of Auditory, Intellectually, and Repetition (AIR) learning model on student’s problem solving skills and to knows the problem solving skills enhancement students who take the learning use Auditroy, Intellectually, and Repetition (AIR). This research is a quasi-experimental reasearch (quasi experiment) with pretest-posttest control group design. The independent variable in this research is Auditory, Intellectually, and Repetition (AIR) learning model and the dependent variable is student problem solving skills. The population in this research are class XI IPA SMA N 2 Banguntapan. The sampling technique is simple random sampling as experiment class is XI IPA 2 and as control class is XI IPA 3. The research instrument used a pretest-posttest question sheet. Data analysis technique used statistical parametric of T test and normalized gain (N-Gain) test. The result showed that (1) Auditory, Intellectually, and Repetition (AIR) learning model influence on problem solving skills of students on the subject of theory kinetic gas (level of significance (sig. 2-tailed) = 0,000 < ? = 0,05, therefore H0 is rejected and Ha is received), (2) Auditory, Intellectually, and Repetition (AIR) model learning can improve students’ problem solving skills on the subject of theory kinetic gas (N-Gain experimental class = 0,886 (high) > N-gain control class = 0,662 (medium).